Banking Reform - Howard Davies; David Miles; Charles Goodhart; Harald Benink; Patricia Jackson; David T. Llewellyn; Thomas F. Huertas; Colette Bowe; Mike Power; Clément Wyplosz (SUERF - The European Money and Finance Forum, 2016)
On 3 December EY hosted a SUERF conference on banking reform with Sir Howard Davies, the Chairman of RBS, and Dame Colette Bowe, the Chairman of the Banking Standards Board, as the two keynote speakers. Professor David Miles (Imperial College) gave the SUERF 2015 Annual Lecture on Capital and Banks. The conference focused on core aspects of banking reform: the amount of capital required, the design of capital requirements (complexity versus simplicity), proportionate regulation, recovery and resolution, and risk culture.
Keywords: E44; E53; F36; G21; G24; G28; G32; G33; 330